Experiences of being a perioperative nurse working in a tertiary government hospital - Phurattanakornkul, Prownapa (วารสารพยาบาลเกื้อการุณย์, 2015)
The purpose of this research was to describe the experiences of being a perioperative nurse working in a tertiary government hospital. Hermeneutic phenomenology of Martin Heidegger was applied as research methodology. Data were collected by using in-depth interviews of 14 perioperative nurses working at a tertiary government hospital and having more than 3 years of working experience. Data were analyzed by using Crist and Tanner’s method of content analysis. The results of the research revealed as follows: 1) The circulating nurse must pay attention to the operation procedure which includes: (1.1) sustain the convenience in the operating room, (1.2) prepare and the operation tools and beware of contamination, (1.3) coordinate with the team and note down, and (1.4) keep the patient safe as the first priority, 2) The scrub nurse must be patient and consider the results of operation, this includes: (2.1) keep calm and avoid conflicts, (2.2) memorize specific technique of each surgeon, (2.3) always be conscious, (2.4) find and replace the missing tools, and (2.5) keep strict sterile technique, 3) Another roles of perioperative nurse, this includes: (3.1) working as teamwork, (3.2) provide patient safety and comfort, (3.3) concern in saving patient’s life, and (3.4) being careful during the operation, because one mistake can lead to complication, and 4) Effect from being the perioperative nurse, this includes: (4.1) eating late and having no time to go to the restroom, (4.2) lifting and carrying heavy patients and instruments can cause muscular pain, (4.3) being risk of smoke hazard and air borne infection, and (4.4) working all day and night can lead to body exhaustion. The study findings of the meanings and experiences could lead to the better management system in an operation room and lead to improve efficiency of perioperative nurses in a tertiary government hospital.